Socio-demographic predictors of knowledge, attitude and practice in relation to Ebola Virus disease among medical and nursing students in a Teaching Hospital - Balami, Lawan Gana (2016)
Introduction: The Ebola Virus disease (EVD) is a re-emerging disease, which in recent years has resulted in global fear and panic. The recent 2014 outbreak in West Africa has been devastating both in terms of death rate and wide spread transmission. There is neither a cure nor vaccine available and poor Knowledge, Attitude and Practices (KAP) among Health Care Workers (HCW) has amplified the spread of the disease. Aims and objectives: The aim of this study was to determine the predictors of KAP regarding the EVD among medical and nursing students in their clinical years of training in University of Maiduguri Teaching Hospital (UMTH) Nigeria. Method: A cross-sectional study was conducted among 423 under-graduate students from the Faculties of Medicine and Nursing at the UMTH Nigeria using multi-stage stratified random sampling. Respondents were first stratified based on field of study and secondly based on year of studies then randomly selected using student rosters. Information on socio-demography as well as KAP was collected using a pretested structured self-administered questionnaire. Knowledge was measured using a three-point scale with responses of either “yes, no or I don’t know”. Attitude was measured using a five-point Likert scale of “1 for strongly disagree to 5 for strongly agree”. Practice was measured using a four-point scale of “1 for never to 4 for all the time”. KAP were categorized as good if the cumulative score was ≥ 70%, otherwise a poor category was assigned. Data was analyzed using IBM SPSS version 22. Descriptive analysis was used for socio-demographic variables as frequencies, measures of central tendency and dispersion. For bivariate analysis, chi-square test was used to test for association between socio-demographic categorical variables and categorized KAP. While Spearman’s rank correlation was used to correlate between continuous socio-demographic variables and continuous KAP scores as well as correlation between KAP. Socio-demographic variables with significant association and correlation from bivariate analysis were entered into the regression model and analyzed to determine socio-demographic predictors of KAP using multiple logistic regression by the Forward Likelihood Ratio method. Results: The response rate was 90.7%. Majority had poor knowledge (59.1%), about 51.8% had good attitude, and a majority (72.8%) had good practice respectively. The socio-demographic predictors of knowledge were age (AOR = 1.164, 95% CI = 1.07 - 1.26), field of study (AOR = 4.64, 95% CI = 2.33 – 9.23) and year of studies (AOR = 2.27, 95% CI = 1.06 – 4.84). For attitude were age (AOR = 1.09, 95% CI = 1.01 – 1.18), field of study (AOR = 1.95, 95% CI = 1.14 – 3.34) and year of studies (AOR = 1.99, 95% CI = 1.08 – 3.67). While the predictors for practice were age (AOR = 1.20, 95% CI = 1.12 – 1.28) and year of studies (AOR = 2.45, 95% CI = 1.11 – 5.40). Conclusion: This study determined socio-demographic predictors of KAP regarding EVD among medical and nursing students during their clinical years of training. The findings showed age, year and field of study to be the significant socio-demographic predictors of KAP, which signifies their relevance. The application of these findings towards improving KAP and subsequently the quality of health care services through better government policies is therefore recommended.